2008
DOI: 10.3122/jabfm.2008.06.070140
|View full text |Cite
|
Sign up to set email alerts
|

Grandparental and Parental Obesity Influences on Childhood Overweight: Implications for Primary Care Practice

Abstract: Background:Community-based studies have suggested a multigenerational pattern of obesity affecting children's risk of overweight, but no national data have substantiated such a pattern. Our objective was to examine the prevalence of overweight [body mass index (BMI) >95th percentile for age and sex] among children aged 5 to 19 in a national sample, stratified by the obesity status of their parents and grandparents.Methods: We used a secondary analysis of the Panel Study of Income Dynamics, Child Development Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 19 publications
4
81
3
Order By: Relevance
“…The 1958 birth cohort has described the relationship between birth-weight of the grandchild and the influence of height by the grandparents (57) . Only one other study by Davis et al (51) , has described a measure of BMI for grandparents. This study is limited, however, by the fact that grand maternal and grand paternal body composition was aggregated in the reported analysis.…”
Section: Prospective Studies With Information On Diet and Parental Bmimentioning
confidence: 99%
“…The 1958 birth cohort has described the relationship between birth-weight of the grandchild and the influence of height by the grandparents (57) . Only one other study by Davis et al (51) , has described a measure of BMI for grandparents. This study is limited, however, by the fact that grand maternal and grand paternal body composition was aggregated in the reported analysis.…”
Section: Prospective Studies With Information On Diet and Parental Bmimentioning
confidence: 99%
“…Children of overweight and hypertensive parents and grandparents are not only more likely to develop hypertension, but also have their BP tracking along the upper percentiles (5,6). Other health conditions like diabetes and cardiovascular diseases has also shown to be associated with childhood overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Children having overweight or obese grandparents or parents are shown to be positively correlated with the risk of overweight and obesity in Korea 7 , Greece 5 and America 8 . A study conducted in Pune, India demonstrated that the prevalence of obesity and metabolic syndrome increased in children with an increase in metabolic syndrome components in parents 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation may be the metabolic state of the children and their families, since it has been shown that a familial predisposition to obesity is associated with a poorer response to treatment [9,10,12,14]. Furthermore, a familial predisposition to obesity has been associated with the development of obesity in childhood [15][16][17][18]. The influence of a familial predisposition to obesity has been described in regards to parents [9,11,12,[14][15][16] especially the weight status of the mother [9,11,15], siblings [10], and grandparents [17,18] indicating that the high prevalence of overweight and obese children is dependent upon obesity among the family members.…”
Section: Introductionmentioning
confidence: 99%